АNTITUSSIVE PHARMACEUTICAL DRUGS ADMINISTRATION IN COMPLEX THERAPY OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN - E.E. Lokshina; O.V. Zaitseva (Union of pediatricians of Russia, 2009)
There is considered the problem of treatment of cough in children with acute respiratory infections in article. In particular, the data on an effective administration of the domestic combined medication framed on basis of medicinal grasses with codeine in complex therapy of acute respiratory infections is presented.Key words: acute respiratory infections, cough, treatment, codeine, children.